Differential effects of low vs. high inertial loads during an eccentric-overload training intervention in rugby union players: a preliminary study - Sabido, R.; Pombero, L.; Hernandez-Davo, J. L. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Eccentric overload training (EOT) has been proposed as an effective stimulus to optimize dynamic athletic performance. Nevertheless, the appropriate intensity during EOT remains unknown. The purpose of this study was to evaluate the influence of the inertial load used during an EOT program on performance adaptations in rugby union players. METHODS: Fifteen rugby players were divided into a low (0.025 kg·m2; G 0.025) or a high (0.075 kg·m2; G 0.075) inertial load for training. Both groups trained using the flywheel half squat exercise twice a week during the seven-week EOT. Athletic performance was evaluated by testing the half squat maximum repetition (1RM), countermovement jump (CMJ), 40 m linear sprint, the modified agility T-Test, and power output in the flywheel squat exercise. Data were analysed using magnitude-based inferences. RESULTS: Both groups improved their 1RM and CMJ to a similar extent. Nevertheless, the G 0.025 showed likely trivial changes in linear sprint (ES=-0.02), and possibly positive effects on the agility T-Test (ES=0.16), while the G 0.075 showed possibly negative effects on 40 m linear sprint (ES=-0.23) and likely trivial effects on the T-Test (ES=0.07). CONCLUSIONS: Due to the similar gains in 1RM and CMJ, and the superior maintenance in linear sprint, the use of low inertial loads during EOT may be a better option when looking for athletic performance optimization.